2018
DOI: 10.1111/tpj.14018
|View full text |Cite
|
Sign up to set email alerts
|

Hair, encoding a single C2H2 zinc‐finger protein, regulates multicellular trichome formation in tomato

Abstract: Trichomes originate from the epidermal cells of nearly all terrestrial plants, which are specialized unicellular or multicellular structures. Although the molecular mechanism regulating unicellular trichome formation has been extensively characterized, most of the genes essential for multicellular trichome formation remain unknown. In this study, we identified an associated locus on the long arm of chromosome 10 using a genome-wide association study (GWAS) on type-I trichomes of 180 diverse Solanum lycopersicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 47 publications
1
101
0
Order By: Relevance
“…Considerable variation in trichome type and density exists in cultivated tomato and its wild relatives, making this a suitable system for trichome study (Simmons and Gurr, 2005; Glas et al , 2012). Monogenic mutants have been described controlling alterations in trichome type and density (Yang et al , 2011 a , b ; Chang et al , 2018). Given the epistatic effects of genetic background, functional comparative studies of mutants are best performed using the same tomato cultivar (Tonsor and Koornneef, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable variation in trichome type and density exists in cultivated tomato and its wild relatives, making this a suitable system for trichome study (Simmons and Gurr, 2005; Glas et al , 2012). Monogenic mutants have been described controlling alterations in trichome type and density (Yang et al , 2011 a , b ; Chang et al , 2018). Given the epistatic effects of genetic background, functional comparative studies of mutants are best performed using the same tomato cultivar (Tonsor and Koornneef, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…C2H2 genes have also been reported to play an important role in determining the epidermal cell fate. As members of the C2H2 genes, GIS, ZFP5, and ZFP6 promote trichome initiation by transcriptional activation of the downstream trichome initiation complex (GL1-GL3-TTG1) [60]. Our results showed that the only C2H2 gene STZ highly expressed during fuzz ber initiation development.…”
Section: Major Transcription Factors Involved In Ber Developmentmentioning
confidence: 59%
“…Therefore, we assessed the expression profiles of the 104 C2H2-ZFs in various tomato tissues using published transcriptomic data (Zouine et al, 2017), revealing that the C2H2-ZF genes display a diversity of relative expression patterns in different organs ( Figure 6) and may therefore play differing roles in various tissues or biological processes. But the homologous genes had similar expression patterns, such as Solyc10g078970.1.1 (SlHair), AT1G68360 (GIS3), AT1G10480 (ZFP5), and AT1G67030 (ZFP6) were all found to be grouped into Group A ( Figure 1A), which were previously reported to play important roles in controlling trichome development (An et al, 2012;Chang et al, 2018;Sun et al, 2015;Zhou et al, 2013). Reported genes, AT5G04340 (ZAT6) and AT1G27730 (ZAT10/STZ), Solyc06g075780.1.1 (SlZF3) and Solyc07g006880.1.1 (SlZFP2) were classified into the Group B ( Figure 1A) and Group IX ( Figure 1B), which showed the similar functions; for example, AT5G04340 (ZAT6) and AT1G27730 (ZAT10/STZ) was involved into the organs development and the adversity stress responses (Devaiah et al, 2007;Mittler et al, 2006), and Solyc06g075780.1.1 (SlZF3) enhanced the salt-stress tolerance in tomato , and Solyc07g006880.1.1 (SlZFP2) was characterized as a repressor to fine-tune ABA biosynthesis during fruit development (Weng et al, 2015), and they showed the higher expression levels during the fruit ripening in tomato ( Figure 6), which will be helpful for dissecting their roles in fruit ripening.…”
Section: Discussionmentioning
confidence: 80%
“…The zinc finger proteins (ZFPs) are one of the largest protein families in plants. These proteins harbor a highly conserved domain, in which a zinc ion is surrounded by cysteine (Cys) and/or functions of the C2H2-ZFPs in many other plants have also been reported, and are often found to be involved in plant development processes such as morphogenesis of cell and trichomes, ripening and senescence (Chang et al, 2018;Moreau et al, 2018;Weng et al, 2015), and stress resistance such as aluminum, drought and salt (Atreyee et al, 2018;Rai et al, 2012). These findings showed that the C2H2-ZFPs are active in multiple physiological processes under stress conditions; however, the functions of the majority of the C2H2-ZFPs in tomato have not been reported.…”
Section: Introductionmentioning
confidence: 99%